Who Are We as Teachers? A Sequential Study of Structuring Teacher Professional Identity among Malaysian Educators - Goh, Kok Ming; Syariff M. Fuad, Dayang Rafidah (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
This study explores and empirically validates the key dimensions shaping Teacher Professional Identity (TPI) among Malaysian teachers through a two‑phase sequential, mixed‑method design. In the first phase, thematic analysis of teacher narratives and reflective accounts identified six interrelated dimensions, namely (i) Personal and Emotional Commitment, (ii) Pedagogical Beliefs and Practices, (iii) Innovation and Technology Integration, (iv) Leadership and Professional Growth, (v) Social Responsibility and Community Engagement, and (vi) Student Empowerment and Impact. In the second phase, the Fuzzy Delphi Method (FDM) was employed with ten expert educators to verify the relevance and consensus of these dimensions. All six dimensions achieved strong expert agreement (d ≤ 0.2), with Pedagogical Beliefs and Practices, Personal and Emotional Commitment, and Student Empowerment and Impact emerging as the most central elements of Teacher Professional Identity. The results reveal that Malaysian teachers’ professional identity is deeply anchored in pedagogical values, emotional engagement, and the transformative empowerment of learners. The validated Teacher Professional Identity framework provides a localized and empirically grounded model that integrates both cognitive‑pedagogical and affective dimensions of teaching. The study contributes to the theoretical enrichment of teacher identity research and offers practical guidance for policy design, teacher professional development, and curriculum innovation aligned with Malaysia’s educational goals.
Keywords: Teacher Professional Identity; Fuzzy Delphi Method; Pedagogical Beliefs; Emotional Commitment; Student Empowerment